Bioinspired hydrogels build a bridge from bench to bedside. (August 2021) - Seidi, Khaled; Ayoubi-Joshaghani, Mohammad Hosein; Azizi, Mehdi; Javaheri, Tahereh; Jaymand, Mehdi; Alizadeh, Effat; Webster, Thomas J.; Yazdi, Amirhossein Ahmadieh; Niazi, Mostafa; Hamblin, Michael R.; Amoozgar, Zohreh; Jahanban-Esfahlan, Rana
Highlights: Hydrogels are soft biomaterials that can be engineered to mimic many aspects of a tissue structure. Hydrogel can be formulated into adhesives as wound dressing or bio-sutures. Hydrogels are platforms to deliver cells into the body for therapy or tissue regeneration. Hydrogels in bulk form or nano-hydrogels formed into vehicles can deliver immunotherapies-from antibody-based to cell-based for cancer therapy. Hydrogels can form the scaffold for bio-inspired wearable or implanted devices to operate a vast range of diagnosis to therapeutics. Graphical Abstract: ga1 Abstract: During million years, Nature has created a "wealthy repertoire of novel features." These features are frequently used in the fabric of artificial materials, referred to as "biomaterials." Hydrogels are among the most attractive biomaterials because they are highly amenable to accept nature-derived properties/functionalities. The inclusion of these features in biomaterials serves as promising tools for today's most urged clinical needs, among others. In this review, we explore the major applications of different bioinspired hydrogels. We focused on rationale design, multi-faceted biomimetics strategies, and their potentials utility in the clinic. For the clinical application, we focused on four major clinical areas of i) regenerative medicine, ii) tissue engineering, iii) cancer therapy, and iv) bioinspired devices/actuators/robots. We discussed how incorporating nature-inspired properties into hydrogels' design can introduce novel solutions to the many unresolved and persistent problems in biomedicine. Finally, given the complexity of bioinspired hydrogels, we propose that a collective effort among the material scientists, artificial intelligence experts, clinicians, and life sciences is required to pave the path for the entrance of bioinspired hydrogel into personalized medicine and from bench to bedside.